ПОДАЛЯК Н.Г. Ганза: мир торговли и политики в ХІІ-ХVІІ столетиях - Ціватий, В. Г. (Український історичний журнал, 1999)
ПОДАЛЯК Н.Г. Ганза: мир торговли и политики в ХІІ-ХVІІ столетиях. - К., 1998. - 202 с.